2018
DOI: 10.17219/acem/74197
|View full text |Cite
|
Sign up to set email alerts
|

Odontogenic effects of two calcium silicate-based biomaterials in human dental pulp cells

Abstract: Based on the cell responses observed in this study, MM-MTA might be used efficiently in dental pulp therapy as a potential alternative to MTA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 25 publications
1
9
1
Order By: Relevance
“…This could suggest a reaction to the implantation of BD, indicating its mineralizing potential, as in cytokine measurements in the present study, this material significantly expressed IL‐8 at 30 days and also expressed mRNA of BMP2 in the same period. As for MTA and BMP2, our study confirmed the findings of Önay et al, 27 but Silva et al 28 showed that MTA stimulates BMP2 expression. This suggests that these affinities could result from the close relationship of BMPs with osteoblasts, where both BMP2 and BMP4 have effects on osteoblasts, 73 making it difficult to elucidate the specific roles during osteogenesis.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This could suggest a reaction to the implantation of BD, indicating its mineralizing potential, as in cytokine measurements in the present study, this material significantly expressed IL‐8 at 30 days and also expressed mRNA of BMP2 in the same period. As for MTA and BMP2, our study confirmed the findings of Önay et al, 27 but Silva et al 28 showed that MTA stimulates BMP2 expression. This suggests that these affinities could result from the close relationship of BMPs with osteoblasts, where both BMP2 and BMP4 have effects on osteoblasts, 73 making it difficult to elucidate the specific roles during osteogenesis.…”
Section: Discussionsupporting
confidence: 91%
“…In addition, only one study to date has assessed the relationship between BMP4 and MTA, thus confirming its osteogenic‐odontogenic potential 26 . As for BMP2, a study has demonstrated no relationship between BMP2 and MTA, only in a special formulation known as MM‐MTA 27 ; however, another study has shown that MTA stimulates BMP2 expression 28 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A similar inflammatory effect was also observed for all materials, in the protein expression of inducible NO synthase and cyclooxygenase‐2 (COX‐2) as well as the expressions of pro‐inflammatory cytokines tumour necrosis factor alpha, interleukin (IL)‐1b, IL‐6 and IL‐8 (Chang et al, 2015). In another study, HDPCs were in indirect contact with MM‐MTA or ProRoot MTA extracts at 1, 7 and 14 days (Önay et al, 2018). Both materials exhibited similar expression levels of odontogenic markers for instance alkaline phosphatase liver/bone/kidney (ALPL), DSPP, runx‐related transcription factor 2 (RUNX2) and distal‐less homeobox 3 (DLX3; Önay et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…e osteodifferentiation of MM-MTA related to increase in alkaline phosphatase activity [77] and the expression of bone morphogenetic protein 2 (BMP2) more than other generations of MTA, and this may be associated with higher concentration of magnesium and sodium [78]. e presence of higher silicon ions in BD stimulates young bone formation by stimulating osteoblasts and promoting mineralization [11].…”
Section: Parametersmentioning
confidence: 99%